1884 Ga. Laws 30, ch. 457 - (:unkn) unknown (General Publisher, 1884)
Required disclosure of guns, pistols, Bowie knives, and "such articles" for property tax purposes.
--
Keywords: TAX - PROPERTY OR SALES